2012
DOI: 10.1248/bpb.35.10
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Apoptosis-Inducing Effects of Lipophilic Vitamins on Human Melanoma A375 Cells in Vitro

Abstract: The effects of six lipophilic vitamins: tretinoin (ATRA), vitamin D(3) (VD(3)), VE, VK(1), VK(3), and VK(5) on cell proliferation and apoptosis in human A375 melanoma cells were investigated. VD(3), VK(3), and VK(5) were found to inhibit cell proliferation significantly at concentration ranges of 10-100 μmol/L (p<0.01), while the other vitamins did not show inhibitory effects at 100 μmol/L. VK(3) and VK(5) showed the strongest effects with IC(50) values of less than 10 μmol/L. Dacarbazine slightly inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
2
23
0
1
Order By: Relevance
“…Notably, whilst DTIC treatment (40 µM) did not induce apoptosis, combined pitavastatin-DTIC treatment resulted in significant levels of apoptosis as evidenced by the increased level of apoptosis markers, cleaved PARP and active caspase 3, as well as annexin V staining. The results of the present study are in agreement with a number of studies which demonstrate that high concentrations of DTIC are necessary to induce apoptosis in melanoma cells (19,32,36). Whilst there has been insufficient research to determine which type of apoptosis is induced by DTIC, sensitization to the intrinsic apoptotic pathway has been revealed to augment DTIC-induced melanoma tumour cell death (37).…”
Section: Discussionsupporting
confidence: 91%
“…Notably, whilst DTIC treatment (40 µM) did not induce apoptosis, combined pitavastatin-DTIC treatment resulted in significant levels of apoptosis as evidenced by the increased level of apoptosis markers, cleaved PARP and active caspase 3, as well as annexin V staining. The results of the present study are in agreement with a number of studies which demonstrate that high concentrations of DTIC are necessary to induce apoptosis in melanoma cells (19,32,36). Whilst there has been insufficient research to determine which type of apoptosis is induced by DTIC, sensitization to the intrinsic apoptotic pathway has been revealed to augment DTIC-induced melanoma tumour cell death (37).…”
Section: Discussionsupporting
confidence: 91%
“…245,257 It has been reported that 1,25(OH) 2 D3 induces apoptosis of WM1341 melanoma, but not MeWo cells. 244 Therefore, it is possible that the pro-apoptotic activity of 1,25(OH) 2 D3 depends on cell-type-specific factors as recently described in the gastric cancer cell line HGC-27 (see recent review ref.…”
Section: Vitamin D and Experimental Models Of Melanomamentioning
confidence: 99%
“…Subsequently, Newton-Bishop and colleagues in a UK study of 872 melanoma patients (5) reported that serum vitamin D levels were higher among those with better overall survival, and Rosso and colleagues in a European study of 260 melanoma patients (6) found that melanoma patients with more sunny vacations prior to diagnosis had better melanoma-specific survival. Laboratory studies have shown that vitamin D suppresses tumor proliferation (7) and suggest that increased vitamin D levels might keep a melanoma “in check”. To test the hypothesis that increased sun exposure prior to diagnosis is associated with improved survival from melanoma, we evaluated measures of solar UVR exposure prior to diagnosis in 3,578 incident melanoma patients in the Genes, Environment and Melanoma study (GEM), an international, population-based study (8).…”
Section: Introductionmentioning
confidence: 99%